2017
DOI: 10.1109/tia.2017.2699164
|View full text |Cite
|
Sign up to set email alerts
|

Design of a High-Speed Ferrite-Based Brushless DC Machine for Electric Vehicles

Abstract: In the present paper an analytic procedure for the preliminary design of a High-Speed ferrite-based Brushless DC Machine (HS-BLDC) has been proposed. In particular, a mechanical and electromagnetic modeling has been developed in order to take into account their mutual influence in the definition of the geometry of the electrical machine. In addition, suitable design targets have been imposed in accordance with electric vehicle application requirements. Hence, several mechanical and electromagnetic constraints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…On experimentation, it found that the inner rotor motor also provides good power characteristics over dynamic conditions. In [32] preliminary algorithm of high-speed ferrite-based BLDC motor is discussed. Magnetic flux components are improvised by adjusting the mechanical constraints.…”
Section: Table II Comparison Of the Inner And Outer Rotor Featuresmentioning
confidence: 99%
“…On experimentation, it found that the inner rotor motor also provides good power characteristics over dynamic conditions. In [32] preliminary algorithm of high-speed ferrite-based BLDC motor is discussed. Magnetic flux components are improvised by adjusting the mechanical constraints.…”
Section: Table II Comparison Of the Inner And Outer Rotor Featuresmentioning
confidence: 99%
“…Therefore, their maintenance cost is low compared to DC motors. Moreover, because of the low cost driving devices and the development of control technology, BLDC motors have been replacing DC motors in various fields [1][2][3][4]. As a double-pole magnetization permanent magnet (PM) has two poles in one magnet, even if the number of magnets is halved, the same number of poles can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, permanent magnet synchronous motors (PMSMs) have been widely used in industries because of their various advantages, such as high-speed operation, high efficiency, and compact design [1][2][3][4]. However, PMSMs have the disadvantages of noise and vibration caused by high magnetic energy during the interaction between stator and rotor magnets; these drawbacks significantly affect machine performance.…”
Section: Introductionmentioning
confidence: 99%